Improvement and development of dynamic screen monitoring and mouse controlling over local area network (LAN) / [disket] - 374649 Kong, Chia Ming (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001